PENGEMBANGAN E-LKPD BERBASIS LIVEWORKSHEET PADA MATERI PENDAPATAN NASIONAL UNTUK KELAS XI DI SMAN GLENMORE BANYUWANGI - Mardiyana, Lisana Oktavisanti; Zanah, Miftakhul; Herlindawati, Dwi (STKIP Paris Barantai, 2025)
The Learner Worksheets (LKPD) currently used in schools have a simple and unattractive printed format. These LKPDs only serve as a tool for providing information without being accompanied by pictures or illustrations, thus making the learning atmosphere boring for students. As a result, they easily lose interest and motivation to complete the task. In addition, teachers revealed that they have never used LKPD in electronic format. This study aims to develop E-LKPDs that comply with the eligibility standards and can meet the needs of students. The method used in the development is ADDIE, which consists of five stages: analyze, design, development, implementation, and evaluation. Based on the results of the material validation test, an average score of 87% was obtained, while the feasibility of the design scored 85.2%, both of which were included in the “very feasible” category. The suitability test showed a score of 84.5%, with the criteria “strongly agree”. Thus, it can be concluded that the liveworksheet-based E-LKPD has met the eligibility and suitability standards for use in the learning process. Keywords: E-LKPD, Model ADDIE, Liveworksheet, National Income